Dopaminergic modulation of axonal potassium channels and action potential waveform in pyramidal neurons of prefrontal cortex. (9th May 2013) - Yang, Jing; Ye, Mingyu; Tian, Cuiping; Yang, Mingpo; Wang, Yonghong; Shu, Yousheng
Key points: Dopamine and its receptors in prefrontal cortex (PFC) play an important role in regulating synaptic transmission and PFC‐mediated cognitive functions. Considering that presynaptic action potential waveform can modulate postsynaptic responses, we investigated whether axonal K + channels and action potential waveform are subjected to modulation by dopamine. Patch‐clamp recording from the axon of PFC pyramidal neurons showed that the activation of D1 and D2 dopamine receptors decreased and enhanced axonal K + currents, respectively. Further experiments revealed that intracellular cAMP–PKA pathway was involved in this dopaminergic modulation of axonal K + currents. Recording from axons disconnected from the soma revealed that the dopaminergic modulation still occurred, indicating the presence of functional dopamine receptors along the axon. We further demonstrate that axonal action potentials were substantially prolonged by D1 receptor activation. Taken together, our results reveal a new mechanism for dopaminergic modulation of neuronal signalling in PFC. Abstract Voltage‐gated K + (KV ) channels play critical roles in shaping neuronal signals. KV channels distributed in the perisomatic regions and thick dendrites of cortical pyramidal neurons have been extensively studied. However, the properties and regulation of KV channels distributed in the thin axons remain unknown. In this study, by performing somatic and axonal patch‐clamp recordings from layer 5 pyramidal neurons of prefrontal cortical slices, we showed that the rapidly inactivating A‐currents mediated the transient K + currents evoked by action potential (AP) waveform command (KAP ) at the soma, whereas the rapidly activating but slowly inactivating KV 1‐mediated D‐currents dominated the KAP at the axon. In addition, activation of D1‐like receptors for dopamine decreased the axonal K + currents, as a result of an increase in the activity of cAMP–PKA pathway. In contrast, activation of D2‐like receptors showed an opposite effect on the axonal K + currents. Further experiments demonstrated that functional D1‐like receptors were expressed at the main axon trunk and their activation could broaden the waveforms of axonal APs. Together, these results show that axonal KV channels were subjected to dopamine modulation, and this modulation could regulate the waveforms of propagating APs at the axon, suggesting an important role of dopaminergic modulation of axonal KV channels in regulating neuronal signalling.